Function of the upper tangle in webs of young Leucauge argyra (Araneae: Tetragnathidae) - Triana Cambronero, Emilia (2011)
Ontogenetic changes in web structure occur in many spiders of different families, but the functional adaptation of differences in web structure is unknown for most species. We describe the ontogenetic changes in web structure of Leucauge argyra (Walckenaer 1842) and test the function of these differences in webs of spiderlings. Webs of early instar spiders have tangles above the orb web that vary from relatively dense to a single thread, from which some threads extend downward, connecting the tangle to the hub of the orb web. The number of threads of the tangle decreases as spiders grow, and in webs of late instars, the tangle is absent. Our experimental results indicate that the tangle and connecting threads increase the stability of the web, possibly reducing the probability of spiral threads sticking to each other with web movements.